Fatores locacionais e o investimento estrangeiro em pesquisa e desenvolvimento: Evidências para o Brasil, Argentina e México - Fernanda de Negri; Mariano Laplane (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– The aim of this paper is to analyze if specific characteristics of host countries contribute to explain foreign investment in research and development. We have estimated two step selection models to explain the decision and the level of R&D investment by multinational companies in Brazil, Argentina and Mexico. The innovation surveys in these three countries were pooled in order to do the estimations. The main results suggest that the size of the market and the interaction between firms and research institutes and universities are important locational factors explaining multinational companies investments in research and development.
Keywords: F21; O33; O54; 330